BIOREFINERY OF MICROALGAE: THE WORLD’S GREEN GEM FOR THE FUTURE SUSTAINABLE DEVELOPMENT - Angga Puja Asiandu; Widya Sari; Ahmad Saefun Naser; Wulan Rahmani Akmal; Dedy Setyawan; Dita Aulia Yulyanita (Biotropia: The Southeast Asian Journal of Tropical Biology)
Article Highlights: - Integrated biorefinery provides economic and environmental benefits - Microalgae produce higher lipid content than plants - Generally, microalgae produce higher carbohydrate contents essential for bioethanol - Biohydrogen produced by microalgae is a future energy source - As a biofertilizer, microalgae promotes plant growth